Completion of a simple technique for the repair of a complex case of exomphalos major - K. Bedi, Nandini; G. Grewal, Alka (International Surgery Journal, 2023)
In 2014 we published a procedure, the Kaul-Bedi technique, by which we used the epithelized covering of a giant exomphalos major, or hepato-omphalocele, to reduce the herniated organs and replace them into the abdominal cavity in stages. We published our technique when we were able to cover the defect with a dual PROVISC prolene mesh. We anticipated a long period of time before we would be able to bring about a primary closure of the abdominal wall defect. Contrary to our expectations, we were able to achieve a primary, complete, muscular closure of the defect within the next three years with removal of the mesh. We are presenting the stages of repair, discussing the complications encountered and the result achieved. We also discuss the advantages and the drawbacks of this procedure.